Safety and clinical activity of pembrolizumab for treatment of recurrent or metastatic squamous cell carcinoma of the head and neck (KEYNOTE-012): an open-label, multicentre, phase 1b trial. Issue 7 (July 2016) - Seiwert, Tanguy Y; Burtness, Barbara; Mehra, Ranee; Weiss, Jared; Berger, Raanan; Eder, Joseph Paul; Heath, Karl; McClanahan, Terrill; Lunceford, Jared; Gause, Christine; Cheng, Jonathan D; Chow, Laura Q
Summary: Background: Patients with recurrent or metastatic squamous cell carcinoma of the head and neck have few treatment options. We aimed to assess the safety, tolerability, and antitumour activity of pembrolizumab, a humanised anti-programmed death receptor 1 (PD-1) antibody, in patients with PD-L1-positive recurrent or metastatic squamous cell carcinoma of the head and neck. Methods: This study was an open-label, multicentre, phase 1b trial of patients with recurrent or metastatic squamous cell carcinoma of the head and neck. Patients were eligible for enrolment if they were aged 18 years or older, had a confirmed diagnosis of recurrent or metastatic squamous cell carcinoma of the head and neck, and had any level of PD-L1 expression (ie, at least 1% of tumour cells or stroma that were PD-L1-positive by immunohistochemistry). Patients received pembrolizumab 10 mg/kg intravenously every 2 weeks. Primary outcomes were safety in the per-protocol population and the proportion of patients with centrally reviewed overall response per Response Evaluation Criteria In Solid Tumors (RECIST, version 1.1). Overall response was analysed in the full analysis set, which was defined as all patients who had received at least one dose of pembrolizumab, had measurable disease at baseline, and one post-baseline scan or patients without a post-baseline scan who discontinued therapy because of disease progression or a drug-related adverse event. The study is registered withClinicalTrials.gov, numberNCT01848834 and is ongoing, but no longer enrolling patients. Findings: Of the 104 patients screened between June 7, 2013, and Oct 3, 2013, 81 (78%) were PD-L1-positive. Of these, 60 patients with PD-L1-positive squamous cell carcinoma of the head and neck were enrolled and treated: 23 (38%) were HPV-positive and 37 (62%) were HPV-negative. Pembrolizumab was well tolerated, with 10 (17%) of 60 patients having grade 3–4 drug-related adverse events, the most common of which were increases in alanine aminotransferase and in aspartate aminotransferase, and hyponatraemia, each occurring in two of 60 patients; one patient developed a grade 3 drug-related rash. 27 (45%) of 60 patients experienced a serious adverse event. There were no drug-related deaths. The proportion of patients with an overall response by central imaging review was 18% (eight of 45 patients; 95% CI 8–32) in all patients and was 25% (four of 16 patients; 7–52) in HPV-positive patients and 14% (four of 29 patients; 4–32) in HPV-negative patients. Interpretation: Pembrolizumab was well tolerated and demonstrated clinically meaningful antitumour activity in recurrent or metastatic squamous cell carcinoma of the head and neck, supporting further study of pembrolizumab as anticancer therapy for advanced head and neck cancers. Funding: Merck & Co.